Hepatotoxicity associated with statins: A retrospective pharmacovigilance study based on the FAERS database. - Lu Zhou; Bin Wu; Yuan Bian; Yun Lu; Ya Zou; Shanshan Lin; Qinchuan Li; Chun Liu (PLoS ONE, 2025)
Background Statins are commonly prescribed in clinical practice and are associated with a high risk of drug-induced liver injury (DILI). This study aims to examine the real-world data on statin-induced liver injury to assess medication safety. Methods All DILI cases reported with statins as primary suspected drugs were extracted based on the US Food and Drug Administration adverse event reporting system (FAERS) from 2004 to 2023. A disproportional analysis was conducted using reported odds ratios (ROR) and information component (IC) to assess the significant association between statins and DILI. Results A total of 7779 statin-associated DILI cases were identified. DILI patients tended to be aged >65 years (45.43%), with more females than males (48.80% vs 43.75%), and 39.95% of DILI patients required hospitalization. Statin-induced DILI cases are most commonly reported with atorvastatin (53.48%), rosuvastatin (20.44%), and simvastatin (19.46%). The DILI signals (ROR; 95% CI) for statins were ranked as follows: fluvastatin (6.90; 5.89-8.10)> atorvastatin (3.09; 2.99-3.19)> simvastatin (2.96; 2.81-3.12)> lovastatin (2.77; 2.17-3.53)> rosuvastatin (2.27; 2.16-2.39)> pravastatin (2.07; 1.81-2.37). Age-stratified analysis showed that a stronger signal was detected in patients (aged ≥65 years) than patients (aged <65 years) for atorvastatin, simvastatin, pravastatin and fluvastatin. The onset time of DILI was significantly different among the different statins (p = 0.014), and simvastatin resulted in the highest mortality rate (12.15%). Conclusion Based on FAERS database, six statins are significantly associated with liver injury, and fluvastatin, atorvastatin, and simvastatin had the greatest risk of DILI.